Persepsi Petani Mengenai Program Ekowisata Subak Sembung Sebagai Subak Lestari Untuk Mendukung Pertanian Berkelanjutan - Ni Gst Ag Gde Eka Martiningsih; Putu Fajar Kartika Lestari; Antonius Padua Jat (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2024)
Ecotourism is an approach that combines environmental conservation with sustainable tourism activities. As an effort to preserve land, ecotourism plays an important role in maintaining ecosystem sustainability, raising environmental awareness, and providing economic benefits to local communities. Subak Sembung is one of sustainable subak for ecotourism program in Denpasar Regency, with concept involves the wise management of natural resources, minimizing negative environmental impacts, and actively involving communities in tourism activities. The objective of this study is to understand farmers' perceptions of the sustainable Subak ecotourism program implemented in Subak Sembung and to identify the challenges faced in its implementation. Respondents were determined using a purposive sampling method, specifically selecting active farmers with their own land, totaling 35 farmers. The research method used was descriptive with Likert Scale analysis. The results showed that farmers strongly support this program, with an average percentage of 89.49%, categorized as very high or strongly agree. This is because every evaluated aspect achieved high average percentages: socio-cultural aspects (92.86%), environmental aspects (92%), institutional aspects (90.3%), technical aspects (87.3%), and economic aspects (85%). This study also identified challenges, both internal, such as limited capital, and external, such as insufficient policy support from the government